(untitled) (International Journal of Engineering and Computer Science, 2017)
This research paper is about the technology used for sending unsolicited messages over Bluetooth to Bluetooth-enabled devices such as cell phones or laptop computers, called Bluejacking. Range of Bluetooth is limited and hence the range of bluejacking is also limited. It is around 10 meters for mobile phones, and about 100 meters for laptops with powerful transmitters. This technology allows phone users to send business cards anonymously using Bluetooth wireless technology. Receiver does not know who has sent the message, but it has the name and model of the phone of bluejacker. People who get to receive such messages should not add the contacts into their address book. Devices that are set in non-discoverable, hidden or invisible mode are not susceptible to bluejacking. But remember it does not hijack the recipient’s phone, as its name suggests, the phone is not under the control of bluejacker at any time. It has been noted that many people are still not aware of this technology. There are other technologies also which are very similar to it. These are Bluebug, Bluesnarfing, Blueprinting, etc. This paper discusses about Bluejacking and is written to make people aware of it, its use, its misconceptions, prevention measures and also considers its advantages, disadvantages and future prospects.